(untitled)
Student-centered /eamlng (nlso cnllod child contorod /esming) is an approach to oducntlon focusing on tho needs of the students, mthor than thoso of othors involved m the l’ducatlonal procoss, such os toachers and admInistrRlors. T/11s approach hes many implications for tho dosign of curnculum, course content, and mreractivif